INFLUENCE OF GLYPHOSATE CONCENTRATIONS ON SPRAY SOLUTION PHYSICOCHEMICAL CHARACTERISTICS AND DRIFT POTENTIAL - Almeida,Dieimisson P. (2020)
ABSTRACT The herbicide glyphosate is sprayed with varying application volumes that result in different concentrations used in the spray solutions. Thus, this study aimed to evaluate the effect of glyphosate concentrations on the potential risk of droplet drift, surface tension of spray solution, and contact angle of droplets on surfaces. Three experiments were conducted in a completely randomized design. Drift potential was evaluated by median volumetric diameter (MVD), percentage volume of droplets with diameter smaller than 100 μm (%V<100 μm), and coefficient of uniformity (Span), with 12 replications. The surface tension of spray solutions and contact angle of droplets were evaluated on Urochloa ruziziensis leaves, paraffin film, and glass, with four replications. Changing glyphosate concentrations in the spray solution changes the droplet spectrum and contact angle on different surfaces due to changes in spray solution physicochemical characteristics, such as surface tension. The increased glyphosate concentrations in the spray solution lead to increased drift potential of droplets, reducing the surface tension and contact angle of droplets on surfaces.